Pengaruh Content Marketing dan Harga Terhadap Keputusan Pembelian Sunscreen Azarine (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Sunan Gunung Djati Bandung Angkatan 2021) - Siti Rahayu; Ruhenda; Suhendi (Teewan Journal Solutions, 2025)
The development of digital technology has made the internet an essential part of modern life. In addition to serving as a source of entertainment and information, the internet also plays a significant role in marketing activities. One of the products that has experienced growing interest in Indonesia is sunscreen. Many brands take advantage of content marketing strategies and competitive pricing to attract consumers. Therefore, content marketing and price have become important factors influencing purchasing decisions. This study aims to determine the effect of content marketing and price on purchasing decisions of Azarine sunscreen, both partially and simultaneously. The research uses a descriptive-verificative method with a quantitative approach. The population consists of students from the Faculty of Islamic Economics and Business at UIN Sunan Gunung Djati Bandung, class of 2021. A total of 88 respondents were selected using the proportionate stratified random sampling technique. Data analysis in this study employed multiple linear regression using SPSS version 26. The results show that content marketing and price have a positive and significant effect on purchasing decisions, both partially and simultaneously. The adjusted R square value of 60.4% indicates that these two independent variables explain the majority of the variation in purchasing decisions.